Evaluación de la producción de biogás a partir de residuos vegetales obtenidos en la central de abastos de Bogotá mediante digestión anaerobia (2016)
This research aims at the development and characterization of residual biomass mainly organic waste, evaluating their chemical, physico-chemical and microbiological to give proper use by the process of anaerobic digestion characteristics. The first specifies literature review just was to determine the stability of the waste throughout the year in the central supply of Bogota being the square largest market in Colombia, and according to this waste had a higher percentage were selected of macro- and micronutrients within which are both plants and fruits; for which they were formulated three mixtures; one for vegetables, one for fruits and mix manure and water control. temperature, moisture, pH, retention time, among others, that directly influence the production of biogas: as variables were evaluated. diagnosis and conditioning of pilot-scale digesters available in facilities central supply was also performed.